PENGARUH INSENTIF DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN PT. BFI FINANCE INDONESIA TBK. CABANG SUNTER - Edward Efendi Silalahi; Ester Rosalina (Juremi: Jurnal Riset Ekonomi, 2023)
Influence of Incentives and Career Development on Job Satisfaction of Employees of PT. BFI Finance Indonesia Tbk. Sunter Branch. This study aims to determine partially and simultaneously the independent variables, namely incentives and career development, on the dependent variable, namely employee job satisfaction. This research was conducted at PT. BFI Finance Indonesia Tbk. Sunter Branch. The method used in this study is a quantitative method, which in this study uses the Saturated Sample technique, namely the entire population is sampled. The population in this study were all employees at PT. BFI Finance Indonesia Tbk. Sunter branch, totaling 74 employees with a sample of 74 respondents. Based on the results of the study, it shows that in the partial test (t) the Incentive variable has a significant effect on employee job satisfaction with a sig value of 0.004 <0.05 and a t-count of 3.019 > t-table 1.99394 and the Career Development variable has a significant effect on employee job satisfaction. with sig value. 0.000 < 0.05 and t-count of 3.805 > t-table 1.99394. Furthermore, in the simultaneous test (f) the Incentive and Career Development variables simultaneously have a significant effect on employee job satisfaction with a sig. 0.000 < 0.05 and f-count of 51.525 > f-table 3.13 then for the determination test (R2) it is found that the correlation between the two variables Incentives (X1) and Career Development (X2) on Employee Job Satisfaction (Y) is 59 ,1%.